Efficacy of Rifaximin Therapy in Patients with Irritable Bowel Syndrome without Constipation- A Tertiary Hospital Based Clinical Trial - Banerjee, Probir Kumar; Roy , Projesh Kumar; Hoque , Mohammad Aminul; Faisal, Mohammad Abu; Chakraborty , Joyashree (The Insight, 2021)
Introduction1: Irritable bowel syndrome (IBS) is a common clinical problem encountered by primary care physicians and gastroenterologists. Studies have demonstrated the variable efficacy of Rifaximin in adult with IBS. Objective: To see the efficacy of Rifaximin, the non-absorbed antibioticwith the placebo in reducing symptoms in adults with IBS without constipation and also compare its side effects with placebo. Methods and Materials: A total of 108 patients from 18-60 years of both sexes with the diagnosis of IBS were selected purposively form the Gastroenterology OPD ofBSMMU. Diagnosis of IBS weremade on the basis of Rome III criteria and who did not have red flags sign. Then all patients underwent screening investigations (Hb%, TC, DC, ESR, Stool R/E, Blood glucose, serum TSH, and short colonoscopy) to exclude organic disease. Improvement was assessed by changes of symptoms monitored by 7 point Likert scale for Global IBS Symptom, abdominal bloating, abdominal pain, 5point stool consistency and average daily bowelmovement. Result: At the end of treatment Rifaximin group showed significant improvement of Global IBSsymptom (Rifaximin vs. placebo 50% vs. 14%). The response was persistent up to 10 weeks after treatment. Other symptoms like bloating, abdominal pain, stool consistency and daily bowel movement improved significantly. But this symptom somewhat deteriorated at the end offollow up (At 70 days after treatment). Conclusion: Rifaximin was effective in reducing Global IBS symptom without constipation and the effect waspersistent. However, it is relatively more effective than placebo. Rifaximin also show significant clinical improvement in bloating, abdominal pain, stool consistency and average daily bowel movement. But the effect was not persistent.